PENGEMBANGAN PERANGKAT SUPERVISI AKADEMIK PENGAWAS PAI SMA NEGERI PURWOREJO - Ikhsan - Buntaran; Mustaqim -; Rifqi - Muntaqo (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2019)
This research is motivated by the limitations and problems of academic supervision of PAI supervisors at State Senior High Schools in Purworejo Regency. This causes the implementation of supervision to be less effective, while supervision is needed to guard educational goals. Improving the quality of teachers has an impact on improving the quality of education. Thus, teachers as one of the determinants of educational success need to get special attention in the form of services and assistance from supervisors. The type of research used is field research and Research and Development (R&D). The research was conducted in eleven public high schools in Purworejo Regency in semester 1 of the 2016/2017 academic year with the research subjects being PAI teachers and PAI supervisors. Data were collected using validation sheets, interviews, questionnaires and observation sheets. The supervision tools and research instruments used have gone through a series of validation stages by experts and trials in limited groups. The supervision tool that has been validated is applied to a population of 26 public high school PAI teachers in Purworejo Regency and one GPAI supervisor. The results showed that the resulting academic supervision tool was valid and ideal, with an average score of 3.6 with good criteria. The calculation results show that the effectiveness increases, with an N-gain of 0.7. This increase is quite high. With these results, it is suggested to GPAI supervisors to develop ideal academic supervision tools according to their respective conditions.